NOMOPHOBIA PADA MAHASISWA UNAIR ( STUDI PADA MAHASISWA TINGKAT AKHIR FKM PSDKU UNIVERSITAS AIRLANGGA DI BANYUWANGI) - Iftitah Amalia Rahmadani; Ayik Mirayanti Mandagi (Journal of Community Mental Health and Public Policy)
ABSTRACT Smartphone is one of the telecommunication equipment, nowadays has become a must-have for everyone. Unfortunately, people do not realize that smartphone use have a negative impact in the form of nomophobia. Nomophobia is a person's anxiety if they cannot access their smartphone. College students are a group that can also be affected by nomophobia. This study aimed to find out the picture of nomophobia in final level students of FKM PSDKU Universitas Airlangga in Banyuwangi. The population used weres 41 people. The research design used descriptive quantitative studies with a cross sectional approach. The research was conducted by providing google form related to Nomophobia Questionnaire (NMP-Q). The results showed that students with the number of 4 people (9.76%) have mild nomophobia and 37 people (90.24%) have moderate nomophobia. The conclusion of the results obtained that all college students of the final level of FKM PSDKU Universitas Airlangga in Banyuwangi experienced nomophobia. It is recommended for students to increase physical activity and social interaction and set a daily schedule of activities in order to do more activities without using a smartphone. Keywords: Nomophobia, Smartphone, Final Students